Evidence of the new economy at the macroeconomic level and implications for monetary policy - Klaus-Jürgen Gern; Carsten-Patrick Meier; Joachim Scheide (Institut für Weltwirtschaft (IfW), 2003)
The notion of new economy was coined in the United States when there was increasing evidence that, as a result of the introduction of new technologies, the traditional behavior of macroeconomic variables might have changed. The expansion of the 1990s differed from its predecessors in three important respects: productivity, inflation, and cyclical variability. In the United States, labor productivity increased much faster in the 1990s than in the previous decades and, contrary to the usual pattern, accelerated with the duration of the expansion. The view that most of the productivity acceleration was only cyclical and therefore not sustainable over a longer period of time has proven overly pessimistic. Productivity growth has remained on its elevated since the economy peaked. In other large industrial countries, by contrast, productivity growth has continued to decline or has improved only very slightly at best. Differences in productivity trends between the United States and other large industrial countries can be explained partly by the fact that in the United States IT production is more important and IT implementation relatively advanced. In addition, the identification of IT-related productivity gains in Europe is complicated by the general trend towards deregulation in labor and product markets and moderate wage increases that contributed to a rise in labor intensity, which tends to lower advances in productivity. In contrast to productivity developments, the behavior of inflation is consistent with a new economy in all large industrial countries. The moderate inflation can, however, be explained by adequate monetary policies and cyclical influences. Similarly, the analysis of cyclical variability concludes that changes in economic policies are a more important factor in explaining the reduced fluctuations in U.S. GDP than the advent of IT. A technology shock which raises the permanent level of output and, at least temporarily, the growth rate of the production potential has implications for monetary policy. In a world with rational expectations and sticky prices, the optimal reaction of monetary policy to an acceleration of potential output growth is to raise interest rates. The reason is that the expectation of higher incomes in the future causes current spending to grow faster than potential output and thus leads to inflationary pressure. In reality the optimal response of monetary policy to a shift in production potential is difficult to assess given the uncertainty concerning the timing and magnitude of new economy effects on the real economy. Being too expansionary probably has more severe consequences than erring on the other side, because the positive real effects would work through anyway, while inflationary expectations, once triggered, are difficult to reduce.
Keywords: 330; E-Business; Produktivität; Geldpolitik; Makroökonomik; Dynamisches Modell; Wirtschaftspotenzial; Theorie; USA; Industriestaaten